2008
DOI: 10.1091/mbc.e06-12-1156
|View full text |Cite
|
Sign up to set email alerts
|

Ste20-related Protein Kinase LOSK (SLK) Controls Microtubule Radial Array in Interphase

Abstract: Interphase microtubules are organized into a radial array with centrosome in the center. This organization is a subject of cellular regulation that can be driven by protein phosphorylation. Only few protein kinases that regulate microtubule array in interphase cells have been described. Ste20-like protein kinase LOSK (SLK) was identified as a microtubule and centrosome-associated protein. In this study we have shown that the inhibition of LOSK activity by dominant-negative mutant K63R-⌬T or by LOSK depletion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…A role for SLK in Plk1 activation during the cell cycle has been recently suggested (Ellinger-Ziegelbauer et al, 2000). Supporting this, SLK was found to be important for microtubule radial array orientation (Burakov et al, 2008).…”
Section: Introductionmentioning
confidence: 77%
“…A role for SLK in Plk1 activation during the cell cycle has been recently suggested (Ellinger-Ziegelbauer et al, 2000). Supporting this, SLK was found to be important for microtubule radial array orientation (Burakov et al, 2008).…”
Section: Introductionmentioning
confidence: 77%
“…Interestingly, SLK demonstrates a dramatic decrease in kinase activity under these adhesion-stabilizing conditions, suggesting a role for activated SLK in the regulation of dynamic focal adhesions [69]. In contrast to its ability to remodel actin, overexpression of SLK does not affect the organization of the microtubule network: SLK has been shown to regulate both microtubule radial array orientation and golgi polarization during interphase, as well as cell cycle progression through G2/M, without affecting microtubule stability [78,80,81].…”
Section: Involvement In Signaling and Migrationmentioning
confidence: 99%
“…39,40 Further study revealed that SLK was required for radial microtubule organization during interphase as depletion of the kinase resulted in the inability of centrosomes to anchor or cap microtubules. 21 Interestingly, overexpression of SLK induced cell cycle re-entry of Xenopus oocytes. 39 These observations offer a possible mechanism by which overexpression of SLK leads to apoptosis.…”
Section: The Multiple Roles Of Slkmentioning
confidence: 99%
“…The carboxy-terminus of SLK shares a high degree of identity with AT1-46 at amino acids 788-936 (63%) and 957-1171 (71%) as well as with LOK (56%) between amino acids 867 and 1178. 14,17,21,22 This C-terminal coil motif was termed the ATH domain, for AT1-46 homology domain. 14,23 A putative caspase 3 consensus cleavage site (DXXD) is also contained within the central domain at amino acid residue 436 of the mouse sequence and is loosely conserved in several other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation